Quality of Service Approach for Wireless Body Area Network Based on Grade - Yujun Ma; Min Chen; Junfeng Wang (Dianxin kexue)
A quality of service framework based on grade for WBAN that have three different grades was proposed. Utilizing time slot-based CSMA/CA of beacon enabled model of IEEE 802.15.4, guaranteed time slot and traffic differentiation,the QoS framework was implemented. Simulation results indicate the QoS framework can meet the QoS requirements of WBAN.